Coactivators p300 and CBP Maintain the Identity of Mouse Embryonic Stem Cells by Mediating Long‐Range Chromatin Structure. (17th June 2014) - Fang, Fang; Xu, Yifeng; Chew, Kai‐Khen; Chen, Xi; Ng, Huck‐Hui; Matsudaira, Paul
Abstract : Master transcription factors Oct4, Sox2, and Nanog are required to maintain the pluripotency and self‐renewal of embryonic stem cells (ESCs) by regulating a specific transcriptional network. A few other transcription factors have been shown to be important in ESCs by interacting with these master transcription factors; however, little is known about the transcriptional mechanisms regulated by coregulators (coactivators and corepressors). In this study, we examined the function of two highly homologous coactivators, p300 and CREB‐binding protein (CBP), in ESCs. We find that these two coactivators play redundant roles in maintaining the undifferentiated state of ESCs. They are recruited by Nanog through physical interaction to Nanog binding loci, mediating the formation of long‐range chromatin looping structures, which is essential to maintain ESC‐specific gene expression. Further functional studies reveal that the p300/CBP binding looping fragments contain enhancer activities, suggesting that the formation of p300/CBP‐mediated looping structures may recruit distal enhancers to create a concentration of factors for the transcription activation of genes that are involved in self‐renewal and pluripotency. Overall, these results provide a total new insight into the transcriptional regulation mechanism of coactivators p300 and CBP in ESCs, which is important in maintaining self‐renewal and pluripotency, by mediating the formation of higher order chromosome structures. Stem Cells 2014;32:1805–1816